New public governance and the North Eastern region of India - Chowdhry, Sachin (2016)
The North-Eastern Region (NER) of India, which consists of eight states, has received focused attention of the Union Government since the 1970s when the North-Eastern Council (NEC) was established under an Act of 1971 of Parliament of India. The persistent backwardness of the region elicited further response from the Union Government in the form of the establishment of Ministry of Development of North-Eastern Region (DoNER). Policy pronouncements like Non-Lapsable Central Pool of Resources (NLCPR) and amendment in the NEC Act tried to address the problems from time to time. This article tries to find the reasons for not so effective intervention of the state and assesses the scope of New Public Governance approach in the NER and the road ahead for speedy development of the region in the national interest, especially
Keywords: Public administration - India, North East; Public administration